Developing the therapeutic conversation: a conversation analysis of information giving in Family Domains Therapy. Issue 1 (19th November 2018) - Pethica, Stefania; Hill, Jonathan; Jones, Katy; Tranter, Paul; Riley, Steve; Lee, Heather; Swales, Michaela
Abstract : Family Domains Therapy is an intervention based on the work of Hill et al . (2014). A key feature of Family Domains Therapy is the provision of information on the model that underpins the therapy. This study is the first to use applied conversation analysis (CA) to explore the interactional impact of giving information regarding a therapeutic model during therapy sessions. Using techniques of conversation analysis this paper offers a description of the four formats therapists used to give information in this therapeutic setting (non‐technical scenarios, 'if X then Y' format, technical paraphrase and formulation format). Additional turn‐by‐turn conversation analysis uncovered how families were more likely to give extended responses when information was given using the format of non‐technical scenarios. Implications of the use of this type of applied conversation analysis for the study of therapeutic processes for future research and clinical practice are discussed. Practitioner points: Practitioners can use different ways of providing information in order to open up or close down topics of conversation Using everyday terminology often leads to family members sharing additional information Using the terminology of the domains model often leads to minimal acknowledgement from family members Corroborating findings from other settings suggest that therapists could use these ways of interacting strategically to structure therapy sessions 抽象: 发展治疗性会话：对家庭领域治疗中信息提供的会话分析 家庭领域治疗是基于希尔等人的研究（Hill et al. 2014）的一项干预。它的一个关键特征是提供关于支持治疗的模型的信息。本研究首次使用应用会话分析（CA）来探讨在治疗过程中提供关于治疗模型的信息的互动影响。本文使用会话分析技巧，描述了治疗师在此治疗环境中提供信息的四种形式（非技术性场景，"如果X就Y"形式、技术性阐释和生成形式）。额外的逐轮对话分析显示，当信息以非技术场景的形式给出时，家庭如何更有可能给出更多响应。本文最后讨论了使用此类应用会话分析来研究治疗过程对未来研究和临床实践的意义。 对实务工作者的启示: 从业者可以使用不同的方式提供信息，以便开启或关闭对话的主题 使用日常用语经常可以使家庭成员分享额外信息 使用领域模型的专业术语常常无法得到家庭成员的认同 来自其他场景的证实性发现表明，治疗师可以利用这些策略性互动的方式来组织治疗 Resumen: Desarrollando la conversación terapéutica: un análisis conversacional de la información que se da en la Terapia de Domios Familiares. La terapia de dominios familiares (FDT, sus siglas en inglés) es una intervención basada en el trabajo de Hill et al. (2014). Una característica clave de FDT es la provisión de información sobre el modelo que sustenta la terapia. Este estudio es el primero en utilizar el análisis de conversación (CA) para explorar el impacto interactivo de proporcionar información sobre un modelo terapéutico durante las sesiones de terapia. Utilizando técnicas de análisis de conversación, este artículo ofrece una descripción de los cuatro formatos que los terapeutas utilizaron para brindar información en este entorno terapéutico (escenarios no técnicos, formato 'si X, luego Y', paráfrasis técnica y formato de formulación). Un análisis adicional de conversación en cada turno de palabra descubrió cómo las familias tenían más probabilidades de dar respuestas extendidas cuando se daba información utilizando el formato de escenarios no técnicos. Se discuten las implicaciones del uso de este tipo de análisis de conversación aplicado al estudio de procesos terapéuticos para futuras investigaciones y prácticas clínicas. Puntos de implicación práctica: Los profesionales pueden usar diferentes formas de proporcionar información para abrir o cerrar temas de conversación El uso de terminología cotidiana a menudo lleva a los miembros de la familia a compartir información adicional El uso de la terminología del modelo de dominios familiares a menudo conduce a un reconocimiento mínimo por parte de los miembros de la familia Los hallazgos que corroboran nuestros resultados en otros entornos sugieren que los terapeutas podrían usar estas formas de interactuar estratégicamente para estructurar las sesiones de terapia